ANALISIS KUANTITATIF KANDUNGAN PROTEIN PADA OLAHAN KERIPIK BUAH - Kristiandi, Kiki; Yunita, Nurul Fatimah; Maryono (JURNAL TEKNOLOGI PERTANIAN, 2024)
Fruit chips are a popular snack among the public, as they have a long shelf life and are easy to carry. This study aims to analyze the protein content in various types of fruit chips, including banana chips, papaya chips, and pineapple chips, using the Kjeldahl method. This method was chosen for its ability to measure nitrogen levels, which can be converted into protein content. The results showed that the protein content in papaya chips ranged from 5.150% to 5.462%, in banana chips from 3.250% to 3.762%, and in pineapple chips from 3.169% to 3.919%. Based on these findings, papaya chips have the highest protein content compared to banana and pineapple chips. Factors influencing the difference in protein content include the composition of the fruit, the processing methods, and the drying techniques used in making the chips. The conclusion of this study is that the Kjeldahl method is effective for analyzing the protein content in various types of fruit chips. Papaya chips have the highest protein content, making them a superior choice in terms of nutritional value compared to banana and pineapple chips. This research is expected to serve as a reference for the development of more nutritious fruit chip products.